Green Project in Kuala Lumpur - Ali Alsaeedi, Yaser Abdulwahab; Mohamed, Sulzakimin; Chau, Sim Yee (Research in Management of Technology and Business, 2020)
Green house is becoming a strong momentum in the construction industry after recognizing many negative environmental issues and problems.  The possible social and economic benefits around the world must be able to make green project a success. Yet, developers still using conventional way to construct the project. This gives huge impact to our environment and also human health. Meanwhile, there are actually some barriers hindering developers to adopt this in their projects. In this study, the perception of stakeholders on green housing will be reviewed. This study could really help our awareness on environment and improve the green project among developers. This study examines the perceptions of the developers in Wilayah Persekutuan on the future of the green project for the next 20 years. The introduction of Green home rating system, improvement of awareness and knowledge among the stakeholders, support from the government and local industry and the effect of competitive advantage should support brighter future for green project. For the moment, the status quo in rules and regulation, lack of public interest and demand, organization disinterest, local authority enforcement and project cost escalation are factors that hinder a faster progress towards green project.